Diagnostic Accuracy of Three Dimentional Digital Substraction Angiography (3D DSA) in Correlation with Computed Tomographic Angiography (CTA) and Magnetic Resonance Angiography (MRA) in Evaluation of Aneurysmal Subarachnoid Haemorrhage - Tabassum Begum, Zubair Janan Orakzai, Mohsin Khan, Bakht Rokhan, Ayesha Kamran, Muhammad Numan Akram, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Subarachnoid hemorrhage is cause by ruptured aneurysms. Early diagnosis is necessary for prevention of the disease. For detection of size and location of intracranial aneurysms in aneurysmal subarachnoid haemorrhage different diagnostic tool are used. The 3D DSA imaging modalities parameters were considered as gold standard in diagnosis of aneurysms. MRA and CTA competencies in diagnosis of ruptured aneurysms were also evaluated. Objective: The aim of the study was to evaluate the sensitivity of 3D DSA, CTA and MRA in diagnosis of intracranial aneurysms in referred patients. The imaging modalities parameters of 3D DSA was considered as gold standard. Study design: It was retrospective observational study with statistical approach. Methods: The 27 consecutive patients of subarachnoid haemorrhage visited the neurology and radiology department of BKMC / MMC Mardan from August 2021 to January 2022 was included in the study. All the patients passed the inclusion criteria while those who are reluctant to undergo through CTA, MRA were excluded. The three dimensional constructed images of each patient underwent through CTA, MRA and 3D DSA were recorded. The obtained data was analyzed for the results. Results: CTA and MRA has variable sensitivity range in diagnosis of intracranial aneurysms. It varied according to the size of aneurysms. For the diagnosis of small sized aneurysms the CTA and MRA has the sensitivity of 57.1 %, while it changes to 88.8 % in diagnosis of medium sized aneurysms. For diagnosis of large sized aneurysms, the CTA and MRA has same sensitivity of 100%. Hence for the detection of small and medium sized aneurysms the sensitivity of CTA and MRA reduced to 20% as compared to the sensitivity of 3D DSA. Conclusion: It was concluded from the results that the 3D DSA is most accurate tool with higher sensitivity for diagnosis of intracranial aneurysms in patients of subarachnoid haemorrhage. The results obtained by using 3D DSA are 20% more sensitive than the results obtained by using CTA and MRA. Keywords: (SAH) Subarachnoid hemorrhage, CTA) Computed Tomographic Angiography, (MRA) Magnetic Resonance Angiography.